2008
DOI: 10.1016/s0828-282x(08)70193-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for contrast media-induced nephropathy and long-term survival: Prospectively assessed data from the randomized controlled Dialysis-Versus-Diuresis (DVD) trial

Abstract: T he development of radiographic contrast media originated from the use of sodium iodide in radiography in 1918 (1), when Walter Dandy directly injected contrast media into the cerebral ventricles for visualizing the outline of the brain and the ventricular system. Since then, many different types of contrast media have been synthesized, and many improvements in terms of side effects, such as hypersensitivity reactions, have been made. Moreover, associated acute renal failure, currently classified as contrast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 19 publications
3
30
0
Order By: Relevance
“…They speculated that abnormalities of renal perfusion possibly mediated by RAS were responsible for development of CIN and administration of captopril offers protection against development of CIN. Holscher et al [11] prospectively assessed predictors of CIN within 72 h and long-term outcomes of 412 consecutive patients with serum creatinine levels of 1.3 mg/dL to 3.5 mg/dL undergoing elective CAG. In their study, patients were randomly assigned to periprocedural hydration alone, hydration plus one-time hemodialysis or hydration plus N-acetylcysteine [11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They speculated that abnormalities of renal perfusion possibly mediated by RAS were responsible for development of CIN and administration of captopril offers protection against development of CIN. Holscher et al [11] prospectively assessed predictors of CIN within 72 h and long-term outcomes of 412 consecutive patients with serum creatinine levels of 1.3 mg/dL to 3.5 mg/dL undergoing elective CAG. In their study, patients were randomly assigned to periprocedural hydration alone, hydration plus one-time hemodialysis or hydration plus N-acetylcysteine [11].…”
Section: Discussionmentioning
confidence: 99%
“…Holscher et al [11] prospectively assessed predictors of CIN within 72 h and long-term outcomes of 412 consecutive patients with serum creatinine levels of 1.3 mg/dL to 3.5 mg/dL undergoing elective CAG. In their study, patients were randomly assigned to periprocedural hydration alone, hydration plus one-time hemodialysis or hydration plus N-acetylcysteine [11]. Multivariate logistic regression identified the predictors of CIN as prophylactic postprocedural hemodialysis (OR 2.86, 95% CI 1.07 to 7.69), use of angiotensin-converting enzyme inhibitors (OR 6.16, 95% CI 2.01 to 18.93), baseline glomerular filtration rate (OR 0.94, 95% CI 0.90 to 0.98) and the amount of contrast material (OR 1.01, 95% CI 1.00 to 1.01).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Because the study was retrospective, medication use was according to the prescribing preferences of individual physicians irrespective of the controversial role of ACE inhibitors in the development of CIN. Some investigators have reported that ACE inhibitors can prevent CIN in patients with diabetes mellitus 16 or chronic kidney disease, 17 and other researchers 18,19 have recommended that administration of ACE inhibitors be discontinued before cardiac catheterization.…”
Section: Methodsmentioning
confidence: 99%